Economic and Social Reintegration of Returnee Migrant Women in Chautara-5, Sindhupalchowk - Rai, Mala (Journal of Multidisciplinary Research Advancements, 2025)
This study explores the economic and social reintegration challenges faced by returnee migrant women (RMW) in Chautara-5, Sindhupalchowk, Nepal. Employing a qualitative approach, the research examines the socio-cultural and economic barriers these women encounter upon returning from foreign employment. Findings reveal that RMW struggles with limited livelihood opportunities, social stigma, and inadequate government support. Despite their contributions to household economies through remittances, many return to financial instability due to a lack of sustainable income sources. The study emphasises the importance of gender-sensitive policies, skill-based training, and community awareness programs to facilitate a smoother reintegration process. Recommendations include enhancing local employment opportunities, improving access to information, and addressing systemic gender inequalities.